HUBUNGAN MINAT BELAJAR DAN CARA BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELASVIII A SMP NEGERI 2 KECAMATAN PAYAKUMBUH - Sri Mures Walef (Ensiklopedia of Journal, 2019)
This research is motivated by the interest and way of learning of less good students so that disturb the process of learning process. For that we need some ways to learn that can help students in learning. The way students learn about Indonesian lessons is influenced by the learning habits that are applied so far. This study aims to reveal the relationship of interest in learning and how to learn the results of learning Indonesian in SMP Negeri 2 Kecamatan Payakumbuh. The type of this research is quantitative research using correlational descriptive method with a population of 230 people. Then taken the sample of this study using cluster sampling technique as many as 27 people. This research uses two variables, variable (X) interest in learning and way of learning and variable (Y) learning outcomes. The steps of data analysis as follows. (1) Correcting and tabulating the questionnaire value; (2) Give a score on each question; (3) Score the results of the Mid Semester 2 exam; (4) Grouping values by rating scale; (5) Correlating data of interest in learning and ways of learning on learning outcomes; (6) Hypothesis testing; and (Summing up the results of data analysis. Data analysis using statistical method with data analysis show: (1) test result prove t_hitung bigger than t_ (table) that is 6,2859 ? 1,708 hence there is relation anatra learn interest with result learn student of class VIII A SMPN 2 Payakumbuh; (2) test result proves t_hitung bigger than t_ (table) that is 6,1617 ? 1,708 hence there is correlation between way of learning with result of study of student of class VIII A SMP Negeri 2 Kecamatan Payakumbuh; (3) test result proves t_hitung bigger than t_ (table) that is 7,2078 ? 1,708 hence there is relation anatra interest learn how to learn with result learn student of class VIII A SMPN 2 Payakumbuh. So it can be concluded there is a relationship between interest in learning and how to learn on learning outcomes.